Implementasi vigenere cipher 128 dan rotasi bujursangkar untuk pengamanan teks - Rihartanto Rihartanto; Riris Kurnia Ningsih; Achmad Fanany Onnilita Gaffar; Didi Susilo Budi Utomo (Jurnal Teknologi dan Sistem Komputer, 2020)
Information that can be in the form of text, image, audio, and video, is a valuable asset that needs to be secured from unauthorized parties. This research aims to study the implementation of Vigenere cipher 128 (VC-128) and square rotation to secure text information. The square rotation is applied to increase the security of the encryption results obtained from VC-128. The randomness of the rotation results was measured using Shannon entropy based on the distance between characters, and the Avalanche Effect measured changes in the encryption results compared to the original text. The square rotation can increase the randomness of the VC-128 encryption results, as indicated by an increase in entropy values. The highest increase in entropy of 34.8 % occurs in repetitive texts with the square size that produces optimal entropy was a 9x9 medium-size square. The Avalanche effect for each test data shows inconsistent results ranging from 44.5 % to 49 %.